2010
DOI: 10.1088/0004-637x/717/1/223
|View full text |Cite
|
Sign up to set email alerts
|

GRB 090417b and Its Host Galaxy: A Step Toward an Understanding of Optically Dark Gamma-Ray Bursts

Abstract: GRB 090417B was an unusually long burst with a T 90 duration of at least 2130 s and a multi-peaked light curve at energies of 15-150 keV. It was optically dark and has been associated with a bright star-forming galaxy at a redshift of 0.345 that is broadly similar to the Milky Way. This is one of the few cases where a host galaxy has been clearly identified for a dark gamma-ray burst and thus an ideal candidate for studying the origin of dark bursts. We find that the dark nature of GRB 090417B -2cannot be expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 77 publications
(85 reference statements)
7
68
1
Order By: Relevance
“…Later an optically dark burst, GRB090417B, showed significant softening after 2 10 s 4´s ince the burst trigger (Holland et al 2010). Very recently a similar spectral softening was also reported in GRB130925A (Evans et al 2014;Zhao & Shao 2014).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Later an optically dark burst, GRB090417B, showed significant softening after 2 10 s 4´s ince the burst trigger (Holland et al 2010). Very recently a similar spectral softening was also reported in GRB130925A (Evans et al 2014;Zhao & Shao 2014).…”
Section: Introductionsupporting
confidence: 55%
“…To successfully interpret the seemingly very complicated afterglow light curves, it would take great effort to develop the external shock models (e.g., Li et al 2015;Wang et al 2015). Alternatively, for the X-ray afterglows that have shallow decay in the light curves and softening in the spectra, an X-ray scattering scenario (Shao & Dai 2007) has been proposed to nicely reproduce both the light curves and spectral evolution (Shao et al 2008;Holland et al 2010;Evans et al 2014;Zhao & Shao 2014). In this scenario a severe optical extinction would also be predicted (Shen et al 2009).…”
Section: Modeling Light Curves and Spectral Evolutionmentioning
confidence: 99%
“…However, GRB 020819 is the first case with known redshift and a well-constrained high extinction value for the entire galaxy. A similar case is that of GRB 090417B (z = 0.345) for which Holland et al (2010) measure A V ∼ 3.5 mag based on the UV and optical SED of this dark GRB host. The high hostgalaxy extinctions of these low-redshift dark GRBs also show that while the dust extinction is one of the main reasons for the darkness of low-redshift bursts, at high-redshift (z > 1) the dust extinction required to dim the afterglow is not that high.…”
Section: Resultsmentioning
confidence: 75%
“…Most of them are precursors (i.e., peaks preceding the main GRB event), but Burlon et al (2008) report on the case of GRB 060210 where two postcursors are observed 60 and 150 s after the end of the main burst. There is no clear example with later time (t ≥ 1500 s) post-cursors, although faint late-time peaks are hardly detectable by BAT (see Holland et al 2010, for a possible candidate). This late-time activity of the central engine could likely be detectable in the X-rays as a peak/flare in the XRT light-curve around the new value of t 0,2 .…”
Section: Discussionmentioning
confidence: 99%